Identification of Soluble Degradation Products in Lithium–Sulfur and Lithium-Metal Sulfide Batteries - Horsthemke, Fabian; Peschel, Christoph; Kosters, Kristina; Nowak, Sascha; Kuratani, Kentaro; Takeuchi, Tomonari; Mikuriya, Hitoshi; Schmidt, Florian; Sakaebe, Hikari; Kaskel, Stefan; Osaka, Tetsuya; Winter, Martin; et al. (Separations, 2022)
Most commercially available lithium ion battery systems and some of their possible successors, such as lithium (metal)-sulfur batteries, rely on liquid organic electrolytes. Since the electrolyte is in contact with both the negative and the positive electrode, its electrochemical stability window is of high interest. Monitoring the electrolyte decomposition occurring at these electrodes is key to understand the influence of chemical and electrochemical reactions on cell performance and to evaluate aging mechanisms. In the context of lithium-sulfur batteries, information about the analysis of soluble species in the electrolytes—besides the well-known lithium polysulfides—is scarcely available. Here, the irreversible decomposition reactions of typically ether-based electrolytes will be addressed. Gas chromatography in combination with mass spectrometric detection is able to deliver information about volatile organic compounds. Furthermore, it is already used to investigate similar samples, such as electrolytes from other battery types, including lithium ion batteries. The method transfer from these reports and from model experiments with non-target analyses are promising tools to generate knowledge about the system and to build up suitable strategies for lithium-sulfur cell analyses. In the presented work, the aim is to identify aging products emerging in electrolytes regained from cells with sulfur-based cathodes. Higher-molecular polymerization products of etherbased electrolytes used in lithium-sulfur batteries are identified. Furthermore, the reactivity of the lithium polysulfides with carbonate-based solvents is investigated in a worst-case scenario and carbonate sulfur cross-compounds identified for target analyses. None of the target molecules are found in carbonate-based electrolytes regained from operative lithium-titanium sulfide cells, thus hinting at a new aging mechanism in these systems.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Batteries; Electrolyte decomposition; Gas chromatography; LiS; Lithium-metal batteries; Lithium-metal sulfide batteries; Lithium-sulfur batteries; Mass spectrometry; Structural elucidation